2013
DOI: 10.1007/s12098-013-1002-2
|View full text |Cite
|
Sign up to set email alerts
|

To Compare the Effect of Dextromethorphan, Promethazine and Placebo on Nocturnal Cough in Children Aged 1–12 y with Upper Respiratory Infections: A Randomized Controlled Trial

Abstract: Nocturnal cough in URI is self-resolving and dextromethorphan and promethazine prescribed for the same are not superior to placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Previous studies showed inconclusive results for the efficacy of cough medicines in the treatment of cold-related cough in adults and children, and it seems that high-quality research is still needed to provide evidence-based recommendations for herbal agents (6)(7)(8). There have been only four clinical trials that compared cough medicines with placebo in children (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed inconclusive results for the efficacy of cough medicines in the treatment of cold-related cough in adults and children, and it seems that high-quality research is still needed to provide evidence-based recommendations for herbal agents (6)(7)(8). There have been only four clinical trials that compared cough medicines with placebo in children (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…The study found that when compared to placebo the treatment arms did not confer any greater benefit with respect to symptom scores. The authors also noted that in the entire cohort there was a propensity for the cough to resolve, irrespective of the intervention type (Bhattacharya 2013). The cohort was evenly divided between groups, with 40 children in each arm.…”
Section: Summary Of Main Resultsmentioning
confidence: 98%
“…We identified no studies eligible for inclusion in this review, and thus found no evidence to support or oppose the use of codeine or derivatives as antitussive agents for chronic cough in children. Our review process identified paediatric studies that evaluated acute cough, in Bhattacharya 2013, Paul 2004, Shadkam 2010, Taylor 1993, and Yoder 2006, and adult-specific chronic cough trials (Barroso 1973;Dierckx 1981;Edwards 1977;Matthys 1983, Matthys 1985Thackray 1978). Of the paediatric-specific RCTs that evaluated acute cough (Bhattacharya 2013;Paul 2004;Shadkam 2010;Taylor 1993;Yoder 2006), none reported any statistically significant difference in cough severity between treatment arm and placebo.…”
Section: Summary Of Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A randomized controlled trial in India comparing dextromethorphan, promethazine, and placebo in children 1 to 12 years of age with URIs found no significant difference in the frequency of nocturnal cough, post-tussive vomiting, or sleep quality. 27 Promethazine has a similar side effect profile to antihistamines (see previous section). Promethazine's abuse potential is fairly high, especially among adolescents and young adults.…”
Section: Promethazinementioning
confidence: 92%